Pendekatan Model Hirarki dalam Menganalisa Faktor-Faktor Pendukung Pengambilan Keputusan Pembelian Mobil: Studi Kasus Wilayah Jakarta Barat - Robert T. Herman; Aditya Artha (Binus Business Review, 2011)
This research is to analyse the consumer purchase decision behaviour in buying cars. The important factor that being considered is product, price, design, comfort, performance, safety, and after-sales service quality. The research objects are city cars including Suzuki Karimun, KIA Picanto, Cherry QQ, and Proton Savvy. Those four products are chosen because they have the highest sales rate on 2007-2008. The sampling technique in this research is probability sampling using cluster random sampling technique. Meanwhile, the analysis method is using analytical hierarchy process (AHP). Finally, it will be concluded the persentage of each factor priority that will affect consumer consideration in purchase decision of each chosen city car. From the seven factors in this research, the result shows that price factor is the most important part and is the main considerable when consumers choose cars.